Uniqueness of the solution to the inverse problem of scattering theory for spectral parameter polynomially dependent Kleın-Gordon s-wave equation - KIR ARPAT, Esra; KÖPRÜBAŞI, Turhan (Tbilisi Centre for Mathematical Sciences, 2023)
In the present work, the inverse problem of the scattering theory for Klein-Gordon s-wave equation with a spectral parameter in the boundary condition is investigated. We define the scattering data set, and obtain the main equation of operator. Furthermore, the uniqueness of the solution of the inverse problem is proved.
Keywords: Matematik; scattering function; scattering data; Scattering theory, inverse scattering involving ordinary differential operators; Scattering theory; inverse problem; scattering data; Levinson formula; inverse problem; Spectrum, resolvent; Levinson formula; Linear boundary value problems for ordinary differential equations with nonlinear dependence on the spectral parameter; Mathematical Sciences; 4. Education